Guibuilder multimodal : um framework para a geração de interfaces multimodais com o apoio de interaction design patterns - Fragoso, Ygara Lúcia Souza Melo (Universidade Federal de São Carlos, 2012)
The interaction between humans and the computers has improved substantially during time through the evolution of interfaces of interaction. The possibility of users to interact with machines through several modalities of communication, and in a natural way, can increase the level of interest from the user and ensure the success of the application. However, the literature of the area of multimodality has shown that developing such interfaces is not a simple task, mainly for non-experienced or recently graduated professionals, since each designer’s modality of interaction has its complexity in technical terms, as acquisition and adaptation with new tools, languages, possible actions and etc. Moreover it is necessary to verify which modalities (voice, touch and gestures) can be used in the application, how to combine these modalities in a way that the stronger point of one completes the weak point of the other and vice versa, and also knowing in what context the final user will be involved. The GuiBuilder Multimodal was developed aiming to try providing the basic needs in implementing an interface that uses voice, touch and gesture. The framework promotes an interface development through the WYSIWYG (What You See Is What You Get) model, where the designer just sets some parameters so the component is multimodal. During the interface creation phase, agents supervise what the designer does and supply support, clues, with design patterns that might be divided in categories such as: multimodality, interaction with the user and components.
Keywords: Interação homem-máquina; Framework (Programa de computador); Usabilidade; Agentes inteligentes; Java; Multimodal interfaces; Design patterns; Usability; IHC; Intelligent agents; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO